Nonalcoholic Fatty Liver Disease (NAFLD) And Cardiovascular Risk In Renal Transplant Recipients - Ivana Mikolasevic; Sanjin Racki; Luka Zaputovic; Vesna Lukenda; Branka Sladoje-Martinovic; Lidija Orlic (Karger Publishers, 2014)
Background/Aims: Renal transplant recipients (RTRs) are at high risk for cardiovascular (CVD) mortality. Recently, nonalcoholic fatty liver disease (NAFLD) has been recognized as a new risk factor for adverse CVD events in the general population. We examined whether transient elastography (TE) defined NAFLD was associated with atherosclerosis in RTRs, as measured by ultrasound in the carotid arteries. Methods: Carotid atherosclerosis was assesses in 71 RTRs with a TE proven NAFLD. With the help of TE liver stiffness was used to assess liver fibrosis and Controlled Attenuation Parameter (CAP) was used to detect and quantify liver steatosis. NAFLD was defined by the presence of steatosis with CAP values ≥238 dB.m-1. Results: RTRs with NAFLD showed more carotid atherosclerosis than RTRs without NAFLD. RTRs-NAFLD patients had the mean intima-media measurements (ITM) of 1.1±0.1 mm and that was statistically significant higher than the mean ITM founded in RTRs without NAFLD (1.1±0.1 vs. 0.9±0.1 mm; pConclusion: We showed for the first time that carotid atherosclerosis is advanced in RTRs with NAFLD. Detection of NAFLD by TE should alert to the existence of an increased cardiovascular risk in RTRs.